Cerámica monocroma esgrafiada/incisa de la Gran Nicoya (siglos i-xvi d.C.) - Gilles Desrayaud (Journal de la Société des Américanistes)
Greater Nicoya Engraved/Incised Monochrome Ceramics (1st-16th centuries A.D.). In order to deepen and complement our knowledge of Precolumbian ceramics from the Greater Nicoya « Subarea », well known for its polychrome paintings, the present study concentrates on the icono-morphological analysis of 326 monochrome engraved/incised vessels and clay objects from museum and private collections. Containers, figurines and musical instruments are decorated with fine figurative modellings and geometrical patterns of complex symbolical significances. After reexamining typology through the available bibliography, we carried out morphological seriations and an iconographic analysis, along with comparisons with ceramics and decorated artefacts from the same and neighbouring areas. The crossing of iconographic data related to the spatial organization of decoration with the functional shapes of vessels and objects helped to demonstrate the Isthmian cultural origins of that tradition, centered on Northwestern Costa Rica as regards Greater Nicoya. It also underlined the gradual expansion of a strong Mesoamerican influence from the 9th century A.D. onwards, corroborating ethnohistorical hypotheses about the arrival of Northeners in the area.